PENGEMBANGAN MEDIA PEMBELAJARAN MENGGUNAKAN SMART APPS CREATOR PADA MATERI BANGUN DATAR SEGITIGA DI KELAS V SEKOLAH DASAR - Mauliana, Desi; Masniladevi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to develop learning media using Smart Apps Creator on the topic of triangular flat shapes in fifth-grade elementary school. The background of this research is the minimal use and utilization of digital technology in learning, despite the school having adequate facilities. This research using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The data obtained is based on validation results by experts, namely subject matter experts, media experts, and language experts. Additionally, data from questionnaires on teacher and student responses, as well as effectiveness tests using the N-Gain Score, were collected. The validation results of the learning media from the experts indicate that the learning media is highly valid, with scores of 84% from subject matter experts, 94% from media experts, and 96% from language experts. Furthermore, the practicality test results show that this learning media is very practical to use, with practicality scores of 96.66% from teachers and 90.66% from students in the trial school. In the research school, the teacher response was 95% and the student response was 91.63%. The effectiveness of using the learning media shows positive results. This is evidenced by the N-Gain Score obtained in the trial school of 0.803447975, research school 1 of 0.836551318, and research school 2 of 0.79750951, all of which fall into the